Validation of the NIMH‐ChEFS adolescent face stimulus set in an adolescent, parent, and health professional sample. Issue 4 (10th September 2015) - Coffman, Marika C.; Trubanova, Andrea; Richey, J. Anthony; White, Susan W.; Kim‐Spoon, Jungmeen; Ollendick, Thomas H.; Pine, Daniel S.
Abstract: Attention to faces is a fundamental psychological process in humans, with atypical attention to faces noted across several clinical disorders. Although many clinical disorders onset in adolescence, there is a lack of well‐validated stimulus sets containing adolescent faces available for experimental use. Further, the images comprising most available sets are not controlled for high‐ and low‐level visual properties. Here, we present a cross‐site validation of the National Institute of Mental Health Child Emotional Faces Picture Set (NIMH‐ChEFS), comprised of 257 photographs of adolescent faces displaying angry, fearful, happy, sad, and neutral expressions. All of the direct facial images from the NIMH‐ChEFS set were adjusted in terms of location of facial features and standardized for luminance, size, and smoothness. Although overall agreement between raters in this study and the original development‐site raters was high (89.52%), this differed by group such that agreement was lower for adolescents relative to mental health professionals in the current study. These results suggest that future research using this face set or others of adolescent/child faces should base comparisons on similarly‐aged validation data. Copyright © 2015 John Wiley & Sons, Ltd.